Detection of Human Parvovirus B19 antibodies in Pregnant Women with Spontaneous Abortion - Hussein, Areej A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Viral infection in pregnancy is known to cause many problems such as fetal malformation; growth restriction and even fetal death; the relationship between viral infection and abortions is not well understood. The infection during pregnancy can affect the fetus due to lack of mother’s immunity. Objective: To assess the frequency of human parvovirus B19-specific antibody type IgM and IgG among pregnant women with spontaneous abortion. Patients and Methods: A semi-quantitative enzyme linked immunosorbent assay technique was applied for detection of anti-human parvovirus B19 IgM (Ridascreen-K6031-Germany) and IgG (Ridascreen -K6021- Germany) in sera of 90 pregnant women who have previously experienced abortion were collected from Al-Batool teaching hospital for maternity and children in Baquba-Diyala province, Iraq, during the period from October 2014 till May 2015. The age was ranged from 18-40 years. Statistical analysis was performed by using statistical package of social sciences, version-16, and P-value of < 0.05 as significant difference. Results: Among study group the mean age was 26.57 years, with an age range 18-40 years. Seropositivity rate was 11.11% (10 cases) for an individual occurrence of human parvovirus B19 IgM alone and 13.33% (12 cases) for a similar individual rate of human parvovirus B19 IgG, while 6 cases (6.66%) had both types of antibodies. Multiple variables regarding occurrence of anti-human parvovirus B 19 specific IgM and IgG antibody simultaneously, was evaluated, and none the variables had significant difference. Conclusion: The fact that 31.11% of studied participants had specific Parvovirus B19 antibody revealed a high occurrence of primary acute parvovirus infection and non-immune against parvovirus B19. Considering the potential role of this virus in abortion and fetal death, it emphasizes the importance of Parvovirus infection in pregnant women also this finding is comparable with that in the other countries.